Android Based LPG Leak Detection Application - Sari, Silvia; Zufria, Ilka; M. Fakhriza (Bahasa Indonesia, 2024)
The educational application of LPG leakage is an innovative solution designed to provide a comprehensive understanding of gas leakage in LPG devices Therefore, it is important for LPG device users requipment to understand the signs of a gas leakage, the actions should be taken, and the preventive steps that can be taken to reduce the risk of accidents and fires. This application provides information that is easy to understand with features for safe handling, tube installation, safety tips along with video tutorials and notifications when there is an LPG gas leakage. With this application, LPG device users will be able to increase their awareness and knowledge about gas leakage. This application can provide ongoing education about the importance of safety maintenance and proper prevention of gas leakage for users, so that can be reduce the risk of serious accidents.